Innovating in a Service-Driven Economy Insights, Application, and Practice - Cuthbertson, Richard; Furseth, Peder Inge.; Ezell, Stephen J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
The global digital revolution has changed consumer society, service expectations, and funding models forever. Value Driven Service Innovation explores these changes from the perspectives of leading thinkers and practitioners in the field of innovation today.
Keywords: Business; Marketing; Management; Leadership; Industrial management; International business enterprises; Economics; Management science; Business and Management; Business Strategy/Leadership.; International Business; Innovation/Technology Management; Marketing; Management; Economics, general; Electronic books